O QUE PODE A PERFORMANCE NA ESCOLA? - André, Carminda Mendes [UNESP] (Centro de Estudos Educação e Sociedade, 2017)
The text presents three master’s studies that deal with the insertion of contemporary art as an area of knowledge in the pedagogical projects of basic education schools. These studies report the pedagogical applicability of these art-education processes with children, adolescents and adults in formal education. The presented result deals with the impact on ethics and political shaping of the students who participated in such processes, as well as problematizes the notions of contemporary art at schools, Arts class and the performance of Arts teachers.

O texto apresenta três pesquisas de mestrado que tratam da inserção da arte contemporânea como área de conhecimento nos projetos pedagógicos de escolas do ensino básico. Tais estudos relatam a aplicabilidade pedagógica desses processos arte-educativos com crianças, jovens ou adultos no ensino formal. O resultado apresentado aborda os impactos na formação ética e política dos estudantes participantes de tais processos, bem como problematiza as noções de arte contemporânea na escola, de aula de artes e de atuação do professor de artes.
What is school performance able to do?
Keywords: School; Performance; Education; Escola; Performance; Educação